2021
DOI: 10.1080/21655979.2021.2001219
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: miR-134-5p promotes inflammation and apoptosis of trophoblast cells via regulating FOXP2 transcription in gestational diabetes mellitus

Abstract: Gestational diabetes mellitus (GDM) is a prevalent and risky pregnant complication which warrants targeted therapy for restriction the inflammation and apoptosis of trophoblast cells. This study sought to analyze the aberrant expression and regulatory mechanism of microRNA (miR)-134-5p in GDM. The miR-134-5p expression in the serum of GDM patients and normal participants was detected via qRT-PCR, followed by receiver operating characteristic (ROC) curve analysis. In vitro GDM cell model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…The 35 included studies ( Table 1 and Table 2 ) were evaluated using the Newcastle–Ottawa Scale (NOS) [ 15 , 54 ], with evaluation criteria listed in Supplementary Materials File S1 , and the NOS evaluations for each included study are displayed in Figure 2 . The average total NOS Score was 59%, ranging from 20% [ 47 ] to 90% [ 17 ]. The diagnosis of GDM was made using national guidelines or IADPSG criteria in 88% of studies (Criteria 3A), while none of the studies clearly described any loss of samples during experiments or data analysis (i.e., failed reactions, eliminated outliers, or absent values; Criteria 3C), although some studies did report number of subjects analyzed for each miRNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 35 included studies ( Table 1 and Table 2 ) were evaluated using the Newcastle–Ottawa Scale (NOS) [ 15 , 54 ], with evaluation criteria listed in Supplementary Materials File S1 , and the NOS evaluations for each included study are displayed in Figure 2 . The average total NOS Score was 59%, ranging from 20% [ 47 ] to 90% [ 17 ]. The diagnosis of GDM was made using national guidelines or IADPSG criteria in 88% of studies (Criteria 3A), while none of the studies clearly described any loss of samples during experiments or data analysis (i.e., failed reactions, eliminated outliers, or absent values; Criteria 3C), although some studies did report number of subjects analyzed for each miRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Patient characteristics were extracted from all included studies to investigate overall heterogeneity regarding included patients. Ten studies diagnosed GDM using IADPSG criteria [ 9 , 19 , 20 , 21 , 24 , 29 , 31 , 33 , 43 , 55 ], seven used ADA criteria [ 17 , 18 , 25 , 28 , 34 , 37 , 38 ], three used national guidelines [ 16 , 36 , 51 ], and one study used WHO criteria [ 22 ], while the remaining studies did not define GDM diagnosis according to any explicit diagnostic criteria ( Supplementary Materials; Data Extraction Sheet ). Patients were generally included with no specific reference to the BMI of patients and control subjects; however, four studies only investigated obese or overweight subjects [ 18 , 20 , 21 , 37 ], and one study only investigated subjects with a BMI < 25 kg/m 2 [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies on circulating miRNAs in relation to GDM have only investigated the expression profile at a single time point in gestation [ 8 , 10 , 11 , 14 , 15 , 16 , 17 , 18 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], with the exception of one study [ 4 ]. There is limited consistency between the investigated miRNAs, although miR-16, -29a, -132, -223 and -330 are reported in more than one study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the induction of miR-134-5p by hyperglycemia in vitro resulted in impaired cell migration and tube formation abilities in endothelial cell progenitors [ 52 ]. Elevated levels of miR-134-5p are associated with both GDM [ 7 , 40 ] and pre-eclampsia and the suppression of infiltration of trophoblast cells [ 53 ], suggesting that dysregulated miR-134 could contribute to GDM pathology. We observed that both miR-433-3p and miR-134-5p were positively associated with gestational weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Integrations of HPV and HBV sequences can induce the expression of prosurvival factors. For HBV, the RIG FOXP2 [66,67] encodes a transcription factor that contributes to preventing inflammation and apoptosis [94]. Similarly, primary oropharyngeal cancer cells show an HPV integration hotspot in intron 10 of BRISC and BRCA1 A complex member 2 (BABAM2) [35], a gene that blocks TNF-α-induced apoptosis [95].…”
Section: Increase In Prosurvival Factorsmentioning
confidence: 99%